Revealing the Atomic Structures of Exposed Lateral Surfaces for Polymorphic Manganese Dioxide Nanowires. Issue 3 (15th December 2020) - Yuan, Yifei; Yao, Wentao; Byles, Bryan W.; Pomerantseva, Ekaterina; Amine, Khalil; Shahbazian‐Yassar, Reza; Lu, Jun
Abstract : Polymorphic 1D MnO2 nanostructures are widely applied in fields such as catalysis, sensing, and energy storage with the functionality mainly determined by the atomic patterns of their laterally exposed facets, which largely remain unclear so far. Herein, by high‐resolution transmission electron microscopy (HRTEM) imaging directly along their axial directions, the atomic structures of the outmost lateral facets of polymorphic MnO2 nanowires are disclosed. To generalize the findings, four most commonly seen phases with characteristic tunnel structures are targeted, i.e., β‐, γ‐, α‐, and todorokite(t)‐MnO2, which are synthesized conventionally using a hydrothermal method reported in the literature. Axially imaging these MnO2 nanowires via HRTEM, the {hkl} facets covering the lateral surfaces are accurately indexed, the atomic pattern of each {hkl} facet is revealed, and it is further coupled with the outmost tunnel configuration that can significantly affect the physicochemical property of MnO2 materials via tunnel‐driven mass adsorption/transport. This work provides a reliable reference for atomic modeling of MnO2 to benefit the pursuit of its structure–property relationship; in addition, it can benefit surface engineering strategies to better rationalize the facet growth control with optimized functionality. Abstract : To reveal the atomic structure of the lateral facets of MnO2 nanowires, single nanowire is subjected to ultramicrotomy and aberration‐corrected scanning transmission electron microscopy. The exposed lateral facets are successfully identified in terms of the plane indexing, atomic patterns, and tunnel configuration. Corresponding atomic models are established with the hope to guide further experimental and theoretical research.